A Novel Citrullinated Modification of Histone 3 and Its Regulatory Mechanisms Related to IPO-38 Antibody-Labeled Protein - Song, Shuzheng; Xiang, Zhen; Li, Jun; Ji, Jun; Yan, Ranlin; Zhu, Zhenggang; Yu, Yingyan (Frontiers in Oncology, 2019)
IPO-38 is a potential biomarker identified in our previous study for diagnosis of gastric cancer. Although we characterized its chemical nature as nucleosome histone, we suspected the existence of histone modification for IPO-38 antibody-labeled protein. In this study, we successfully identified the type and site of histone modification labeled by IPO-38 monoclonal antibody by means of commercially available modified histone peptide array. In protein array analysis, the strongest signaling is citrullination modification of histone 3 on arginine 26 site (H3R26Cit). This histone modification was catalyzed by peptidyl arginine deiminases 4 (PADI4). By construction of PADI4 eukaryotic expression vector and PADI4 CRISPR/Cas9 vector, we confirmed the crucial function of PADI4 on increased level of H3R26Cit. In addition, we found there is an interaction between H3R26Cit and its H3K27me3 by immunoprecipitation and immunoblotting. Our study firstly established a link between IPO-38 antigen with citrullinated histone 3, and clarified upstream regulatory enzyme PADI4. The new findings suggest an important role of citrullination modification of histone on cancer biology of gastric cancer, and helps us optimizing sensitivity and specificity on development of diagnostic reagent.